Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry